KAJIAN PERBANDINGAN PENYEDERHANAAN BIROKRASI PADA JABATAN ADMINISTRASI KE JABATAN FUNGSIONAL PEMERINTAHAN NEGARA INDONESIA DENGAN PEMERINTAHAN NEGARA SINGAPURA - Afriman Oktavianus (Gapenas Publisher, 2023)
Simplification of Bureaucracy in Administrative Positions to Functional Positions or more often known by other terms, namely